(untitled) (Neo Scientific Peer Reviewed Journal, 2025)
The professional training system plays an important role in developing the professional competence of directors of preschool educational organizations (PDOs). This system serves to increase the pedagogical, organizational, managerial and innovative potential of directors. The professional training process allows not only to acquire new knowledge and skills, but also to effectively apply them in practical activities. This article analyzes the tasks, advantages of the professional training system in the formation of professional competence of directors of PDOs and its importance in improving the quality of education.